2021
DOI: 10.1088/1755-1315/648/1/012187
|View full text |Cite
|
Sign up to set email alerts
|

Application of ameliorants for of ex-tin mining soil improvement and increasing corn (Zea mays) yield

Abstract: Ex-tin mining land is a degraded land with low soil fertility and poor soil physical properties. The research aimed to find the best ameliorant for the improvement of ex-tin mining soil and corn yield. This experiment, conducted in Bangka Belitung Province, Indonesia, used a Randomized Block Design with 7 treatments and 4 replications: control, 20 t ha−1 biochar, 20 t ha−1 cattle manure, 20 t ha−1 mucuna compost, 10 t ha−1 biochar+10 t ha−1 cattle manure, 10 t ha−1 biochar+10 t ha−1 mucuna compost, and 10 t ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Soils with a high Na content cause damage to soil structure and increase osmotic pressure so that the absorption of water and plant nutrients is disrupted (Wakeel, 2013). The addition of ameliorants can reduce the exchanged Na content (Ethika et al, 2021) so that it is in the range between low to high. Soil analysis conducted 25 days after the application of amelioran showed that the average Na exchange rate was higher and decreased in soil analysis 48 days after application of amelioran.…”
Section: The Chemical Characteristics Of the Soil In The Research Loc...mentioning
confidence: 99%
“…Soils with a high Na content cause damage to soil structure and increase osmotic pressure so that the absorption of water and plant nutrients is disrupted (Wakeel, 2013). The addition of ameliorants can reduce the exchanged Na content (Ethika et al, 2021) so that it is in the range between low to high. Soil analysis conducted 25 days after the application of amelioran showed that the average Na exchange rate was higher and decreased in soil analysis 48 days after application of amelioran.…”
Section: The Chemical Characteristics Of the Soil In The Research Loc...mentioning
confidence: 99%
“…Another amendment material that is quite popular lately is biochar. Biochar could improve soil chemical properties (Yulnafatmawita et al 2020;Ethik et al 2021;Solfianti 2021), soil biological properties (Dermiyati et al, 2017;Nurbaity et al, 2019), and soil physical properties (Yulnafatmawita et al, 2021;Prakongkep et al, 2021;Gelardi et al, 2021;Fu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%